Have You Yet Found Home?. Issue 177 (1st June 2016) - Irmer, Thomas
Matthias Lilienthal's directorship at the Kammerspiele began with the construction of a series of sleeping units scattered throughout Munich whose costs were not to exceed 250 euros. The apartments drew attention to the everday topic of conversation about the too expensive and at the same time vacant apartments in the city, whereby the project entered the spaces of social life. Such installations become a theatre project when temporary dwellers move in and are then seen as part of the performance by spectators passing by.